2023
DOI: 10.14744/eej.2023.39306
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Prescribing Antibiotics for Management of Patients with Endodontic Infections

Abstract: Objective This study aimed to evaluate the efficacy and duration of antibiotic therapy with different regimens of antibiotics for patients presenting with primary and secondary endodontic infections. Methods In a case series outcome study, all patients needing antibiotics due to endodontic infection were included. In patients with no history of hypersensitivity to penicillin, amoxicillin was used as the first-line antibiotic, followed by adding metronidazole if the symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, Ayazi and Esfehani (4) reported that the frequency of systemic diseases among clients referring to the Qazvin Faculty of Dentistry was 32%. Also, Al-Bayaty et al (9) in India, Mesgarzadeh et al (15) in Tehran, and Parirokh et al (12) in Tehran, Mashhad, and Kerman reported 42%, 41%, and 33.8%, respectively, as the prevalence of systemic diseases in the clients referring to dentistry faculties and private dental offices. In studies by Khader et al (16) in northern Jordan, Amirchaghmaghi et al (17) in Mashhad, and Kumar and Rajan (18) in southern India, the frequencies of systemic diseases were reported at 58.6%, 73.3%, and 52.8%, respectively, which are larger than the values reported in the present research.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, Ayazi and Esfehani (4) reported that the frequency of systemic diseases among clients referring to the Qazvin Faculty of Dentistry was 32%. Also, Al-Bayaty et al (9) in India, Mesgarzadeh et al (15) in Tehran, and Parirokh et al (12) in Tehran, Mashhad, and Kerman reported 42%, 41%, and 33.8%, respectively, as the prevalence of systemic diseases in the clients referring to dentistry faculties and private dental offices. In studies by Khader et al (16) in northern Jordan, Amirchaghmaghi et al (17) in Mashhad, and Kumar and Rajan (18) in southern India, the frequencies of systemic diseases were reported at 58.6%, 73.3%, and 52.8%, respectively, which are larger than the values reported in the present research.…”
Section: Discussionmentioning
confidence: 95%
“…In studies by Rezaei Estabraghi et al (7), Al-Bayaty et al ( 9), Mesgarzadeh et al (15), Kumar and Rajan (18), and Bayat et al (20), similar to the present study, hypertension and diabetes were reported as the most prevalent conditions. In addition, Taghibakhsh et al (11) reported hypertension and thyroid disease, Parirokh et al (12) reported cardiovascular diseases and hypertension, Ayazi and Esfehani (4) reported cardiovascular diseases and digestive disorders, and Khader et al (16) reported digestive disorders as the most frequent systemic diseases. Based on the present study and the mentioned ones, it can be found that the prevalence of all systemic diseases, especially hypertension and diabetes, has been growing in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation